2022
DOI: 10.1093/pnasnexus/pgac017
|View full text |Cite
|
Sign up to set email alerts
|

Minimum complexity drives regulatory logic in Boolean models of living systems

Abstract: The properties of random Boolean networks have been investigated extensively as models of regulation in biological systems. However, the Boolean functions (BFs) specifying the associated logical update rules should not be expected to be random. In this contribution, we focus on biologically meaningful types of BFs, and perform a systematic study of their preponderance in a compilation of 2,687 functions extracted from published models. A surprising feature is that most of these BFs have odd “bias”, that is the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(63 citation statements)
references
References 52 publications
6
57
0
Order By: Relevance
“…In this section, we present the results of our analyses of the abundances of composed BFs in a compiled reference biological dataset of 2687 BFs from 88 published Boolean network models of biological systems [23]. In Appendix C, we provide details about the compilation and curation of this empirical dataset.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section, we present the results of our analyses of the abundances of composed BFs in a compiled reference biological dataset of 2687 BFs from 88 published Boolean network models of biological systems [23]. In Appendix C, we provide details about the compilation and curation of this empirical dataset.…”
Section: Resultsmentioning
confidence: 99%
“…We also computed the number and fraction of composed BFs for different composition structures which have odd bias. Recently, some of us showed that BFs with odd bias are preponderant among BFs in reconstructed Boolean network models of biological systems [23]. Furthermore, it was shown that NCFs [69] and RoFs [23] have odd bias .…”
Section: E Comparing Restriction Levels: Composition Structures Vs Bi...mentioning
confidence: 99%
See 3 more Smart Citations